2023
DOI: 10.1186/s12888-023-05130-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear relationship between sleep midpoint and depression symptoms: a cross-sectional study of US adults

Jiahui Yin,
Huayang Wang,
Siyuan Li
et al.

Abstract: Background Despite the close relationship between sleep–wake cycles and depression symptoms, the relationship between sleep midpoint and depression symptoms in adults remains understudied. Methods In this cross-sectional study, 18280 adults aged ≥ 18 years from the National Health and Nutrition Examination Survey (NHANES) 2015–2020 were analyzed. Covariates included age, sex, race/ethnicity, education level, marital status, family income, body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous studies on the association between sleep midpoint and depressive symptoms examined sleep midpoint at only one time point, which failed to capture long-term changes in individual sleep–wake rhythms 13 , 25 27 . Not surprisingly, variability of sleep midpoint between individuals can be considerable, particularly in the absence of social constraints 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the association between sleep midpoint and depressive symptoms examined sleep midpoint at only one time point, which failed to capture long-term changes in individual sleep–wake rhythms 13 , 25 27 . Not surprisingly, variability of sleep midpoint between individuals can be considerable, particularly in the absence of social constraints 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The exposure variable in this study was sleep duration. NHANES collected self-reported sleep duration data through their standardized questionnaire, which is administered to participants during in-person interviews 57 . In the survey, participants were asked, "How much sleep (hours) do you usually get during the weekdays or during workdays at night?…”
Section: Measurement Of Exposure and Outcome Variablesmentioning
confidence: 99%
“…Current evidence tended to show that extreme short sleep (e.g., sleep deprivation) was associated with several neurological diseases, such as stroke, 11 Alzheimer's, 12 Parkinson's disease, 13 and depression. 14 Amyloid‐β, a protein fragment, has been identified as a key player in the relationship between short sleep and cognitive decline. 15 , 16 Interestingly, emerging evidence suggested that one‐night short sleep duration may be associated with alterations in the clearance or production of amyloid‐β in the brain.…”
Section: Introductionmentioning
confidence: 99%